2016
DOI: 10.1007/s12035-016-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

CRMPs Function in Neurons and Glial Cells: Potential Therapeutic Targets for Neurodegenerative Diseases and CNS Injury

Abstract: Neurodegeneration in the adult mammalian central nervous system (CNS) is fundamentally accelerated by its intrinsic neuronal mechanisms, including its poor regenerative capacity and potent extrinsic inhibitory factors. Thus, the treatment of neurodegenerative diseases faces many obstacles. The degenerative processes, consisting of axonal/dendritic structural disruption, abnormal axonal transport, release of extracellular factors, and inflammation, are often controlled by the cytoskeleton. From this perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 152 publications
0
28
0
Order By: Relevance
“…; Nagai et al . ). We previously reported that excessive alcohol consumption promotes the mTORC1‐dependent translation of CRMP2 in the NAc, resulting in increased microtubule assembly (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Nagai et al . ). We previously reported that excessive alcohol consumption promotes the mTORC1‐dependent translation of CRMP2 in the NAc, resulting in increased microtubule assembly (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…CRMP1, a member of the the Collapsin Response Mediator Proteins (CRMPs) family, regulates many aspects of cytoskeletal remodeling and arborization of neurites and dendrites in neuronal cells (Yamashita and Goshima, 2012 ; Quach et al, 2015 ; Nagai et al, 2017 ). Phosphorylation status of CRMP1 affects the signaling pathways mediated by Semaphorin 3A (SEMA3A) and reelin (Yamashita et al, 2006 ); notably, the latter was an up-regulated gene in our wtPPT1 overexpressing cells (see Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 5 top canonical pathways involved in our analysis are represented in Table 2. It is interesting that CRMP (collapsin response mediator protein) family was highlighted in the analysis as part of the Semaphorin signaling in neurons, since this signaling cascade is known to play an important role in neuronal differentiation and axonal growth [29,30]. Previous studies also concluded that the overexpression of the truncated isoform of DISC1 leads to dysregulation of Semaphorin signaling [20].…”
Section: Ingenuity Pathwaymentioning
confidence: 99%